The Influence of Organizational Culture and Work Engagement on Service Performance Through Service Quality at the West Tanjung Jabung District Health Office - Lestari, Puji; Bukit, Pantun; Akbar, Ali (Journal of Accounting and Finance Management, 2025)
This study aims to describe the implementation of organizational culture, work engagement, service quality, and employee performance at the Tanjung Jabung Barat District Health Office. It also aims to determine and analyze the influence of organizational culture and work engagement through service quality on employee performance. This study was conducted at the Tanjung Jabung Barat District Health Office. The population was 1,021 health workers within the Tanjung Jabung Barat District Health Office with civil servant status in 2024. The sample size used Slovin's theory with a 10% margin of error, resulting in 92 health workers with civil servant status. This study used a quantitative approach with a survey method and Partial Least Square (PLS) data analysis. The results showed that organizational culture and work engagement have an influence on performance, both directly and indirectly through service quality at the Tanjung Jabung Barat District Health Office. This indicates that the Tanjung Jabung Barat District Health Office is able to build a strong organizational culture and is able to proactively involve itself in work, which will be able to improve the quality of service and performance of the Tanjung Jabung Barat District Health Office.